Customary Law as Living Law in Environmental Forest Governance: A Sociology of Law Perspective on Legal Pluralism - T. Romi Marnelly; Resdati Resdati; Dian Kurnia Anggreta; Defri Yoza; Seger Sugiyanto (Jurnal Hukum, 2026)
This study examines the role of customary law in governing the Ghimbo Pomuan Customary Forest in the Kampa Region, Indonesia, within an environmental socio-legal framework. It investigates how customary law functions as a living legal system and how it interacts with state forestry regulations and village governance under conditions of legal pluralism. A qualitative socio-legal approach was employed, combining doctrinal legal analysis and empirical fieldwork. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using Miles and Huberman’s interactive model with thematic coding. Theoretically, the study draws on living law, legal pluralism, and cultural ecology perspectives. Findings show that customary law in Kenegerian Kampa operates as a dynamic normative system grounded in Adat Bersendikan Syara and Syara Bersendikan Kitabullah, and institutionalized through ecological norms, sanctions, and the tigo tungku sajorangan coordination mechanism. However, its interaction with state law reveals structural tensions and institutional fragmentation between forestry and village governance. Although Constitutional Court Decision No. 35/PUU-X/2012 and Ministerial Regulation No. 9 of 2021 formally recognize customary forests, implementation remains weak and disjointed. The study concludes that the key challenge is not legal recognition but insufficient institutional integration across governance levels, limiting the effectiveness of customary forest governance.